AI and cloud computing - Hurson, A. R.; Wu, Sheng (Advances in computers, 2021)
AI and Cloud Computing, Volume 120 in the Advances in Computers series, highlights new advances in the field, with this updated volume presenting interesting chapters on topics including A Deep-forest based Approach for Detecting Fraudulent Online Transaction, Design of Cyber-Physical-Social Systems with Forensic-awareness Based on Deep Learning, Review on Privacy-preserving Data Comparison Protocols in Cloud Computing, Fingerprint Liveness Detection Using an Improved CNN with the Spatial Pyramid Pooling Structure, Protecting Personal Sensitive Data Security in the Cloud with Blockchain, and more. Provides the authority and expertise of leading contributors from an international board of authors Presents the latest release in the Advances in Computers series Includes the latest information on AI and Cloud Computing.